A proposed evaluation of a membrane separation process using reverse osmosis system analysis (ROSA) software - Costales, Fernandina F. (1999, 1999)
Seawater desalination offers an alternative solution to water scarcity problems. In fact, a lot of seawater desalination plants are already in existence in countries abroad. This study is conducted to determine the viability of constructing and operating a local seawater desalination plant. THe early stages of the research were described as the selection of suitable site and appropriate desalination technique. THere were three provinces considered under site selection, i.e. Batangas, Bataan and CEbu, and among those three, CEbu emerged to be the most suitable site. Mactan ISland was chosen as the specific location since the area has groundwater resources. Under the process selection, reverse osmosis appeared to be the most appropriate technique for altwater desalination. Its selection was accounted mainly on its economics and its applicability to various types of feedwater.
The selection process was followed by the evaluation of market, technical and financial viability of the project. THe market study dealt with water supply and demand, and the identification of plant capacity. The wide variance between the projected water demand and supply in Metro Cebu justified the need for new water projects in the area. The plant capacity was identified to be ten thousand cubic meters per day (10,000 cu.m/day). The technical study, on the other hand, focused mainly on the design of auxiliary equipment and of the reverse osmosis train through Reverse Osmosis System Analysis (ROSA)software. ROSA was developed by Dow Filmtec for analysis of membrane and system performance parameters. Lastly, the financial study assessed the profitability of the project by identifying its net present value (ROR), payback period and rate of return. Two financing schemes were evaluated, i.e 10 years and 25 years loan period. A selling price of P63.00 per cubic meter was obtained in both schemes to produce an ROR of more than 20 percent and a positive NPV. The sale of desalinated water together as well as the quality of the product waster was found to be competitive in industrial and commercial areas. As against bottled mineral water, the desalinated water was found to be a lot cheaper.
Thesis (M.S. Environmental Engineering)--University of the Philippines Diliman.
Keywords: Saline water conversion -- Reverse osmosis process -- Philippines -- Mactan Island; Membrane separation; Saline water conversion plants -- Philippines